ANALISIS HUKUM TENTANG PERJANJIAN KERJASAMA YANG DILAKUKAN SALAH SATU PESERO CV TANPA PERSETUJUAN DARI PESERO LAIN (STUDI KASUS PUTUSAN PENGADILAN NEGERI MEDAN NOMOR 369/PDT.G/2006/PN.MDN) - DESMA MARIA TONDANG (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Sunarmi2. Mahmul Siregar3. Syafnil Gani One of the business companies is CV (Commanditaire Vennootschap or or limited partnership) which is established by some people who are liable both jointly and severally as moneylenders. Cooperation agreement between one of the shareholders of a CV and the third party is aimed to give profit for the former although it is not in accordance with the statutes of CV so that it suffers financial loss. The background of the research includes three problems as follows: how about the position of shareholders in CV, how about the validity of cooperation agreement made by one of the shareholders without the consent of the other shareholders, and how about legal consequence of cooperation agreement made by one of the shareholders without the consent of the other shareholders.Keywords: Commanditaire Vennootschap, Cooperation Agreement, Shareholder